If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4x + 2) = 7(x + -4) Reorder the terms: 2(2 + 4x) = 7(x + -4) (2 * 2 + 4x * 2) = 7(x + -4) (4 + 8x) = 7(x + -4) Reorder the terms: 4 + 8x = 7(-4 + x) 4 + 8x = (-4 * 7 + x * 7) 4 + 8x = (-28 + 7x) Solving 4 + 8x = -28 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 4 + 8x + -7x = -28 + 7x + -7x Combine like terms: 8x + -7x = 1x 4 + 1x = -28 + 7x + -7x Combine like terms: 7x + -7x = 0 4 + 1x = -28 + 0 4 + 1x = -28 Add '-4' to each side of the equation. 4 + -4 + 1x = -28 + -4 Combine like terms: 4 + -4 = 0 0 + 1x = -28 + -4 1x = -28 + -4 Combine like terms: -28 + -4 = -32 1x = -32 Divide each side by '1'. x = -32 Simplifying x = -32
| -1(x-19)=-18 | | -4x+5y= | | 175.84=3.14r^2 | | 10x^2+45x-1000=0 | | 4.93-1.2-x=0.5 | | 6x-3x-8=9x | | X+46= | | -8(7a-7)=336 | | 8z+14=7z+2 | | 2/3(y-4/5)=-1/5(y-6) | | -16t^2+24t+4=9 | | .000022-.00044x=x^2 | | 18=6-(z+7) | | -6x-11=4x+19 | | 45-3(n)=5+n | | x(x+10)+24=0 | | 4=0.5-4 | | p(0)=-2x^3+8x-6 | | 6x+17=8x+1 | | -|16|?16= | | 2(8x)+44x=180 | | (8x^2-3x^3)-(6x^2-5x^3)= | | -6y+11=-2x+11 | | 41-2n=2+9 | | -4t^2+766=200 | | 0=-2x^3+8x-6 | | 7(11x+22)+x=-10x | | (3x^4+5y^2)(7x^4+5y^2)= | | 4n-28=2+9n | | -x^2-20x-19=0 | | y=-6/5-2 | | 3-3z=21 |